A model for predicting acute heart failure in patients with acute myocardial infarction by taking into account energy and adipokine metabolism indicators - M.Yu. Koteliukh (Medičnì Perspektivi, 2022)
Acute heart failure (AHF) is one of the most common complications of acute myocardial infarction (AMI). Currently, adropin, irisin, fatty acid binding protein 4 (FABP 4) and C1q/TNF-binding protein 3 (CTRP 3) are considered to be valid markers of energy homeostasis and the adipokine system in AMI patients. The aim of the study was to predict the development of AHF in AMI patients by taking into account indicators of energy homeostasis and adipokine system using generalized linear mixed model. The study examined 189 patients with acute ST-segment elevation myocardial infarction. Concentrations of adropin, irisin, insulin, FABP4 and CTRP3 were determined by enzyme-linked immunosorbent assay. Fasting capillary blood glucose level was measured by glucoseoxidase method. Insulin resistance (IR) was assessed using homeostasis model assessment of insulin resistance (HOMA-IR). The study identified thrombolysis in myocardial infarction (TIMI) grade before intervention. A generalized linear mixed model was used to develop a method for predicting AHF in AMI patients. The study showed decreased levels of adropin, irisin and CTRP3 and increased levels of FABP4 in AMI patients. A mathematical model for predicting AHF development in AMI patients was proposed. The model consisted of fixed effects, namely, two one-factor indicators (HOMA-IR and systolic blood pressure (BP)), one two-factor indicator (systolic and diastolic BP) and one three-factor indicator (adropin, irisin and CTRP3) and random effects such as four one-factor indicators (FABP4, TIMI Grade Flow, platelets, total cholesterol). The accuracy of predicting the absence of Killip class I AHF was 100%, Killip class II AHF – 0%, Killip class III AHF – 11%, Killip class IV AHF – 82%. It should be noted that systolic BP on day 1 was a strong negative prognostic factor, while HOMA-IR, the combined effect of adropin, irisin and CTRP3, the combined effect of systolic and diastolic BP were positive prognostic factors. Thus, the model showed a very high sensitivity in predicting Killip class IV AHF. The overall accuracy of the model was 89.4%.